On the time variability of gamma-ray sources: A numerical analysis of variability indices - Torres, Diego F. (2001)
We present a Monte Carlo analysis of the recently introduced variability indices tau (Tompkins 1999) and I (Zhang et al. 2000 & Torres et al. 2001) for Gamma-ray sources. We explore different variability criteria and prove that these two indices, despite the very different approaches used to compute them, are statistically correlated (5 to 7 sigma). This conclusion is maintained also for the subset of AGNs and high latitude (|b| > 10 deg) sources, whereas the correlation is lowered for the low latitude ones, where the influence of the diffuse galactic emission background is strong.